N-carbamylglutamate enhances pregnancy outcome in rats through activation of the PI3K/PKB/mTOR signaling pathway. - Xiangfang Zeng (Public Library of Science (PLoS), 2012)
Administration of N-carbamylglutamate (NCG), an analogue of endogenous N-acetyl-glutamate (an activator of arginine synthesis) has been shown to enhance neonatal growth by increasing circulating arginine levels. However, the effect of NCG on pregnancy remains unknown. This study examined the effects of NCG on pregnancy outcome and evaluated potential mechanisms involved. Reproductive performance, embryo implantation, and concentration of amino acids in serum and uterine flushing, were determined in rats fed control or NCG supplemented diets. Ishikawa cells and JAR cells were used to examine the mechanism by which NCG affects embryo implantation. Dietary NCG supplementation increased serum levels of arginine, onithine, and proline, as well as uterine levels of arginine, glutamine, glutamate, and proline. Additionally, it stimulated LIF expression, and enhanced the activation of signal transduction and activator of transcription 3 (Stat3), protein kinase B (PKB), and 70-kDa ribosomal protein S6 kinase (S6K1) during the periimplantation period, resulting in an increase in litter size but not birth weight. In uterine Ishikawa cells, LIF expression was also enhanced by treatment with arginine and its metabolites. In trophoblast JAR cells, treatment with arginine and its metabolites enhanced Stat3, PKB, and S6K1 activation and facilitated cellular adhesion activity. These effects were abolished by pretreatment with inhibitors of phosphatidylinositol 3-kinase (wortmannin) and mammalian target of rapamycin (rapamycin). The results demonstrate that NCG supplementation enhances pregnancy outcome and have important implications for the pregnancy outcome of mammalian species.